Lysosomes Associated Diseases and Methods to Study Their Function - Dhiman Sharma, Pooja (IntechOpen, 2017)
This book covers current advances in disorders associated with lysosomal function along with techniques to study its function. All chapters are complete in themselves but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors on lysosomal diseases and opens new possible research paths.